In the post-crisis world, did debt and equity markets respond differently to high-tech industries and innovative firms?. (May 2021) - Cowling, Marc; Liu, Weixi; Zhang, Ning
The belief that more general capital constraints are exacerbated and magnified in innovative and technology-based firms has provided justification for policy intervention, across the range of equity and debt-based financial instruments. In this article, we tackle the question as to whether smaller innovative firms, both in and outside of high-tech industry sectors, do indeed face greater constraints when seeking to access capital from external markets. Our results show that both high-tech and innovation are important determinants of the firms' demand for external finance, but these effects are more pronounced in equity markets than debt markets. On the supply side of capital markets, being in a high-tech industry sector was relatively unimportant from the point of view of financiers. Rather, being involved in innovative activity was associated with a greater incidence of absolute and partial rationing and also in terms of the general process of applying for finance being substantially more difficult. These findings were more acute for firms in high-tech industry sectors that were also engaged in innovative activity. Our findings also suggest that policy makers need greater clarity and nuance when developing policy responses around high-tech and broader innovation activity which, although they have significant overlap, should not be conflated.